Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

Solve the system by substitution. 9y = x - 4x + y = -35 Submit Answer

Sagot :

Let:

[tex]\begin{gathered} 9y=x\text{ (1)} \\ -4x+y=-35\text{ (2)} \end{gathered}[/tex]

Replace (1) into (2):

[tex]\begin{gathered} -4(9y)+y=-35 \\ -36y+y=-35 \\ -35y=-35 \\ y=1 \\ \text{ Replace y into (1)} \\ x=9(1) \\ x=9 \end{gathered}[/tex]